Onset of menarche: differences between urban and rural community in Tangerang District, Banten Province, Indonesia - Suryono Yudha Patria, Dewi Darmawati Sunartini Hapsara (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2012)
The transition of physical and sexual maturation in becoming an adult occurs in adolescenceperiod. This transition runs in parallel with the development of cognitive, emotional, socialcultural and adaptation ability. Girls sexual maturity is marked by first menstruation (menarche)which is the most important phase of reproductive development. The relationship betweenmenarche and growth rate of body height is very close. The menarche occurs when the growthrate of the body height begins to decline. Many factors influence the onset of menarche i.e.physical activity, nutritional intake, socio economic and environmental conditions and availabilityof medical services. These factors vary between rural and urban area. Girls in urban area tend tohave modest life style compared with their counterpart in rural area. The purpose of this studywas to compare the onset of menarche of girls in urban and rural area, and to identify factorsthat influence the onset of menarche. This was a cross sectional study involving 220 girlsstudents of elementary school from both urban and rural area in Tangerang District, BantenProvince. The mean onset of menarche of all subjects was 11.46 ± 0.99 years, while the meanonset of menarche of girls who live in rural area (11.87±0.99 years) was significantly slowerthan girls who live in urban area (11.05±0.80 years) (p=0.01). The birth body weight and birthbody length, physical activity and environment condition significantly influenced the onset ofmenarche. The girls who live in urban areas had an earlier predictor factors to achieve for onsetof menarche than those who live in rural areas (OR: 3.34 [95% CI: 1.911 to 5.823] and aOR:2.95 [95% CI: 1.410 - 6.012]).Keywords: menarche - growth spurt - sexual maturity - urban - rural community